Financial Reporting in the Time of COVID-19 (analysis of financial and non-financial information disclosed by companies from “WIG30 Index” listed on the Warsaw Stock Exchange - one year after the outbreak of the pandemic) - Bogusław WACŁAWIK (Communications of International Proceedings, 2021)
The Covid-19 pandemic has created the highest level of global economic uncertainty. The appearance of virus can be considered as the "Black swan". The motivation to take up the topic of the article results from the enormous perturbations caused by virus in health, social and, above all, economic life. The studies attempted to demonstrate the impact of Covid-19 on the financial performance of enterprises. The main goal of the paper is to present the impact of Covid-19 on the financial results of listed companies from the WIG30 index of the Warsaw Stock Exchange (WSE) one year after the outbreak of the pandemic. The article also analyzes the impact of the coronavirus on going concern, the level of disclosure of reporting information on risks related to Covid-19 and whether the analyzed companies benefited from government assistance (so-called anti-crisis shield). The research has shown that Covid-19 had a significant impact on the financial data presented in the financial statements of companies. In the case of CCC SA, the management board was forced to issue shares to maintain liquidity. Food production, stationary trade and Internet commerce achieved financial record results. The results of banks show that individuals and enterprises repay their loans to a high degree, which may prove their good financial condition. The pandemic triggered a decline in profits in the mining sector. The dangers of the coronavirus pandemic are still there. The article was prepared based on a review of domestic and foreign literature, market analyses of consulting companies  and financial statements of companies from the Warsaw Stock Exchange (WIG30 Index).
Keywords: Covid-19; IFRS; Poland; Warsaw Stock Exchange (WSE).